Pengaruh Brand Awareness Terhadap Purchase Decision Pada Marketplace Tokopedia - Permata, Mindi; Kurniawan, Bayu; Setyorini, Noni (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2023)
This study aims to determine the effect of Brand Awareness on purchase decision in the Tokopedia Marketplace. The population of researchers is all employees of PT Pan Pacific Jakarta Semarang Branch with a total of 2060 employees, the sample that has been determined in this study is 335 employees using probability sampling techniques with simple random sampling methods using the slovinh formula. Data analysis in this study used the SPSS AMOS 24 program. Hypothesis testing with the SEM AMOS approach. The results of the analysis and discussion show that partially the Brand Awareness variable has a positive effect on Purchase Decision in the Tokopedia Marketplace for Employees of PT.Pan Pacific Jakarta Semarang Branch